Characterization of polyurethane produced by polyol synthesized from corn oil - Aydoğmuş, Ercan; Kamışlı, Fethi (Fırat University, 2022)
In this study, biopolyol has been synthesized from corn oil by epoxidation, hydroxylation, neutralization, and purification processes. The rheological properties of both corn oil and polyol obtained from corn oil have been compared. When the variation of viscosity with temperature is examined, it is seen that corn oil-based polyol is more viscous than corn oil. Accordingly, it is thought that the molecular structure of the biopolyol changes, and its molecular weight increases. According to the results obtained, the hydroxyl number of the synthesized polyol is determined as approximately 160 mg KOH/g polyol by the analytical method. The produced polyols have been prepared for polyurethane production after being characterized physically and chemically. The production of polyurethane sponge with a suitable process and method has been realized according to the purpose of use. The approximate density of the produced polyurethane was 40 kg/m3 and the thermal conductivity coefficient was found to be 0.026 W/m·K. Also, Taguchi method has been used in experimental studies to determine an efficient and economical process in both the polyol synthesis and the polyurethane production.
Keywords: Chemical Engineering; Kimya Mühendisliği